The influence of thermal treatment and type of insoluble poly(meth)acrylates on dissolution behavior of very soluble drug from hypromellose matrix tablets evaluated by multivariate data analysis - Kubova, Katerina; Peček, Daniel; Hasserová, Kristýna; Doležel, Petr; Pavelková, Miroslava; Vyslouzil, Jakub; Muselík, Jan; Vetchy, David (Pharmaceutical development and technology, 2017)
Hypromellose matrices exhibit extended burst effect immediately after contact with aqueous medium, especially when a water-soluble drug is incorporated. The objective of this study was to reduce burst effect and maintain complete dissolution of a very soluble levetiracetam over 12 h period from hypromellose K4M matrices to obtain zero-order kinetics. Desired changes were achieved by applying water dispersions of insoluble Eudragits® (NE, NM, RL, RS) as a granulation liquid to the drug/microcrystalline cellulose mixture during high-shear granulation (non-thermal treated set) and consequently by thermally treating granules or final tablets (TT), respectively. Applying Eudragit® water dispersions to the drug/microcrystalline cellulose mixture was recognized as an effective method of significantly reducing the burst release (25.4-33.7%) of levetiracetam in comparison with a reference sample without Eudragit®. Multivariate data analysis showed that the addition of Eudragit® reduced burst effect, increased fitting with zero-order kinetics, and supported matrix erosion as the supplementary mechanism to predominant diffusion. Moreover, resulting PCA sub-model revealed the addition of Eudragit® RL and thermal treatment of tablets to be the most suitable method of all. For a 12 h dissolution profile, characterized by low burst effect and drug release close to 100% at the 12th hour, sample RL_TT was the most suitable.
Keywords: Anticonvulsants; matrix tablets; Hypromellose Derivatives; piracetam; RL; Temperature; Delayed-Action Preparations; HPMC; Eudragit® NE; antikonvulziva; levetiracetam; Multivariate Analysis; celulosa; teplota; Prolonged drug release; rozpustnost; deriváty hypromelózy; Piracetam; Drug Liberation; uvolňování léčiv; multivariate data analysis; NM; Polymethacrylic Acids; tablety; multivariační analýza; Levetiracetam; Cellulose; Drug Compounding; Solubility; léky s prodlouženým účinkem; příprava léků; RS; burst effect; kyseliny polymethakrylové; Tablets; thermal treatment